Study of the expression of oncoprotein p53, EGFR in colorectal carcinomas with different proliferative activity - I.S. Shponka; I.K. Kharkhalis; O.V. Poslavska (Medičnì Perspektivi)
Colorectal cancer, according to the International Agency for Research on Cancer, was and remains an urgent problem worldwide. In 2020, in Ukraine, morphological verification of new cases of colon and rectal cancer was carried out at a high level (83.2% and 89.5%, respectively), but despite this, specific treatment covered only 69.4% and 74.5% of eligible patients, that is why about a third of patients (30.8% of colon cancer patients and 25.0% of rectal cancer patients) did not live even a year from the moment of its detection in 2020. The aim of the study was to evaluate the prognostic significance of the expression of p53 and EGFR markers depending on the clinical, morphological characteristics and proliferative activity of colorectal carcinomas. The clinical and anatomical material of 37 patients (15 women and 22 men) was studied in the work. The age of the patients ranged from 27 to 82 years; the average age was 61.43±14.90 years. Antibodies to Ki-67, p53, EGFR and the UltraVision Quanto visualization system (LabVision) were used for immunohistochemical research. Digital morphometry was performed in the Fiji platform with the calculation of percentages of p53 and Ki-67-positive intranuclear reactions with the ImmunoRatio plugin. The distribution of p53 expression variants - wild type (0<p53 <10%) or "mutant" (overexpression ≥10% or completely negative samples) showed no significant difference in any group (all p>0.05), despite that among men, mutant expression of p53 was significantly higher than among women – 72.72% (16 out of 22) versus 53.33% (8 out of 15), and all patients under the age of 50 years had a mutant type of p53 expression 9 out of 9 (100%), while the number of such observations after 50 years already decreased to about half – 15 out of 28 (53.57%). The distribution of EGFR expression variants showed a significant difference in subgroups according to grade (p<0.05) and in subgroups with different proliferative potential according to Ki-67 (p<0.05).